Dampak Diskriminasi Gender terhadap Resiliensi Perempuan dalam Kepemimpinan Politik Systematic Literature Review - Intan Nur’aini; Nadia Najwa Putri; Bilqis Nabila Afriza; Marsha Ovika Aulia; Salistiya Ursyida; Khoiriya Ulfa (CV. ITTC INDONESIA, 2026)
This study aims to analyze the impact of gender discrimination on women’s resilience in political leadership through a Systematic Literature Review (SLR). The issue is important because women in politics continue to face gender stereotypes, patriarchal norms, media bias, symbolic violence, and limited access to leadership positions. These conditions generate psychological pressure that affects women’s political participation and leadership sustainability. This study assumes that gender discrimination significantly influences women’s resilience in maintaining their roles in politics. The method used is a Systematic Literature Review by analyzing 20 national journal articles published between 2015 and 2025, obtained from Google Scholar, Garuda, and SINTA databases. The findings indicate that gender discrimination negatively affects women’s self-confidence, emotional well-being, and political participation. However, women develop resilience through social support, organizational experience, political education, self-efficacy, and adaptive coping strategies. Resilience enables women to survive and remain active in patriarchal political environments. The study concludes that strengthening psychological resilience and creating inclusive political environments are essential to support women’s leadership and gender equality in politics.